2021
DOI: 10.20944/preprints202110.0104.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Fungal Keratitis in the United Kingdom 2011-2020: A 10-Year Study

Abstract: Fungal keratitis (FK) is a serious ocular infection that often poses significant diagnostic and therapeutic dilemmas. This study aimed to examine the causes, clinical characteristics, outcomes, and prognostic factors of FK in the UK. All culture-positive and culture-negative presumed FK (with complete data) that presented to Queen’s Medical Centre, Nottingham, and Queen Victoria Hospital, East Grinstead, between 2011 and 2020 were included. A total of 117 patients (n=117 eyes) with FK were included i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…IK is a painful and potentially sight-threatening condition that often requires intensive medical and/or surgical interventions (Khor et al, 2018 ; Ting et al, 2021b ). Complications such as corneal melt, perforation, endophthalmitis and complete loss of the eye may sometimes ensue despite intensive treatment (Khor et al, 2018 ; Cabrera-Aguas et al, 2021 ; Ting et al, 2021b , c ). A timely and accurate diagnosis is often the key to a successful clinical outcome, though this is not always possible in clinical practice due to various barriers ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…IK is a painful and potentially sight-threatening condition that often requires intensive medical and/or surgical interventions (Khor et al, 2018 ; Ting et al, 2021b ). Complications such as corneal melt, perforation, endophthalmitis and complete loss of the eye may sometimes ensue despite intensive treatment (Khor et al, 2018 ; Cabrera-Aguas et al, 2021 ; Ting et al, 2021b , c ). A timely and accurate diagnosis is often the key to a successful clinical outcome, though this is not always possible in clinical practice due to various barriers ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…IK is a painful and sight-threatening condition that often requires intensive medical and/or surgical interventions. Several risk factors have been implicated in IK, including contact lens wear, trauma, ocular surface disease, and post-corneal surgeries, amongst others (Edwards et al, 2009;Khoo et al, 2019;Ting et al, 2021a;Ting et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal keratitis is a serious infectious corneal disease with a high rate of blindness [11][12][13]. For fungal keratitis, existing drugs mostly have low penetration, many side effects, and increasing drug resistance [14].…”
Section: Introductionmentioning
confidence: 99%
“…For fungal keratitis, existing drugs mostly have low penetration, many side effects, and increasing drug resistance [14]. Penetrating keratoplasty is often required in severe cases, but the lack of donor material makes treatment difficult [12,15,16]. Since Iseli et al reported 5 cases of fungal and bacterial infections successfully treated by CXL [17], scholars have increasingly applied it in the treatment of infectious corneal ulcers, and different CXL protocols have achieved good efficacy in both in vitro and in vivo studies [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%